Manipulating Bimetallic Nanostructures With Tunable Localized Surface Plasmon Resonance and Their Applications for Sensing - Min, Yuanhong; Wang, Yi (Frontiers in Chemistry, 2020)
Metal nanocrystals with well-controlled shape and unique localized surface plasmon resonance (LSPR) properties have attracted tremendous attention in both fundamental studies and applications. Compared with monometallic counterparts, bimetallic nanocrystals endow scientists with more opportunities to precisely tailor their LSPR and thus achieve excellent performances for various purposes. The aim of this mini review is to present the recent process in manipulating bimetallic nanostructures with tunable LSPR and their applications for sensing. We first highlight several significant strategies in controlling the elemental ratio and spatial arrangement of bimetallic nanocrystals, followed by discussing on the relationship between their composition/morphology and LSPR properties. We then focus on the plasmonic sensors based on the LSPR peak shift, which can be well controlled by seed-mediated growth and selective etching. This review provides insights of understanding the “rules” involving in the formation of bimetallic nanocrystals with different structures and desired LSPR properties, and also forecasts the development directions of plasmonic sensors in the future.